Investigation of the archeological remains using ultrahigh resolution mass spectrometry. Issue 4 (August 2019) - Kostyukevich, Yury; Kitova, Alexandra; Zherebker, Alexander; Rukh, Shah; Nikolaev, Eugene
Investigation of the archeological material at the molecular level can reveal the composition of ancient paint, balsamic material, reveal cooking recipes, etc. High-resolution mass spectrometry is a powerful technique with underestimated potential for archeology. Here, we present the investigation of the 3000-year-old archeological remains, identified as parts of internal organs of an Egyptian mummy, using high-resolution Orbitrap mass spectrometry. We observed a diverse number of oxidized classes of compounds: O, O2, O3, O4, O5, N, NO, NO2, NO3, NO4, NO5, N2 O, N2 O2 . Such chemical composition is unusual and we never observed it in our previous studies of petroleum, humic substances, products of wood pyrolysis or other natural complex mixtures. It is possible that such compounds are formed via biodegradation of lipids and other organic material used for funeral rites. We did not observe evidence of the presence of mineral bitumen, although there are many historical records of the use of mineral bitumen for mummification.